Legal Validity of Transfer of Land Rights Based on a Deed of Sale and Purchase Agreement That Has Been Canceled According to Indonesian Positive Law - Annas, Mujib Medio; Kamello, Tan; Purba, Hasim; ., Saidin (Journal of Ecohumanism, 2025)
According to the provisions of Article 37, paragraph 1 of Government Regulation Number 24 of 1997 concerning Land Registration, the transfer of land rights and ownership rights to apartment units can only be registered if it is made with a deed by a Land Deed Making Officer. Every transfer of land rights must be registered at the local land office. Then, the registration process at the land office must meet all provisions in the Regulation of the Minister of State for Agrarian Affairs / Head of the National Land Agency Number 3 of 1997 concerning Provisions for the Implementation of Government Regulation Number 24 of 1997 concerning Land Registration. However, in practice, the transfer of land rights is often preceded by a deed of Sale and Purchase Agreement and a Deed of Power of Attorney to Sell. This study will examine the legal validity of authentic deeds regarding the transfer of land rights that have been cancelled according to Indonesian positive law and the legal consequences of the transfer of land rights based on authentic deeds that have been cancelled according to Indonesian positive law. The type of research used in this study is the normative legal research method, namely research conducted on applicable laws and regulations or library legal research methods. The nature of the research used in writing this thesis is descriptive and analytical. In the Making of a PPJB Deed for land and buildings, it should no longer be followed by a Deed of Power of Attorney for Sale, just a PPJB, because the Deed of Power of Attorney for Sale creates new legal problems, besides being able to deceive who the real owner of the Object is because of the Deed of Power of Attorney for Sale. In the cancellation of PPJB and Power of Attorney for Sale, the deed that was cancelled must be withdrawn and attached to the minutes of the Deed of Cancellation so that the deed that was cancelled can no longer be used to carry out legal acts and submit the original Certificate that was cancelled to the real owner.